Analyzing the Presidential Power Constraints and the DPR Power Enhancement in the Indonesian 1945 Constitution: A Critical Approach - Saepullah, Saepullah; Ichlas, Rudy Iskandar; Rustan, Ahmad; Jufri, Nur Nashriani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study delves into an examination of how the 1945 Constitution establishes multiple constraints on the President's authority while bolstering the influence of the DPR (People's Consultative Assembly). The research aims to comprehensively analyze the scope of powers granted by the 1945 Constitution to both the President and the DPR. Employing a normative research methodology, this investigation reveals that the 1945 Constitution places specific limitations on the President while strengthening the authority of the DPR through various means. Notably, the Constitution imposes term limits solely on the President, not on the DPR. Although the President participates in the legislative process, certain restrictions apply, and certain powers are granted to the President as the head of state, but they necessitate the involvement of the DPR. In contrast, specific rights exclusively pertain to the DPR in support of its duties, without extending these same rights to the President. Such a scenario underscores the imperative of establishing a constitutional balance of power between the executive authority of the President and the legislative authority of the DPR.